Activities of in vitro laboratory of National Institute of Nuclear Medicine and Allied Sciences (Bangladesh Journal of Nuclear Medicine, 2017)
The in vitro laboratory of radioimmunoassay (RIA) Division is designed to provide clinical diagnostic service (e.g. hormone assay) and also to facilitate research works related to radioimmunoassay. The in-vitro laboratory is situated at the 9th floor of  block-D of Bangabandhu Sheikh Mujib Medical University (BSMMU). Presently the invitro division of National Institute of Nuclear Medicine and Allied Sciences (NINMAS) has 18 man powers including doctors, radiochemists, officers, technologists and other laboratory staffs. The equipments used for RIA in in vitro laboratory are gamma counter, micropipettes, centrifuge, magnetic separators, vortex mixture, incubator/water bath, stirrers, deep freezer, refrigerator, pH Meter, analytical balance, test tubes and laboratory glassware etc.A large number of samples are analyzed by the RIA Lab each week. In the year 2013 - 2014 (1st July 2013 – 30th June 2014), a total of 100 assays were done. A total of 25135 samples were assayed by RIA/IRMA in the in vitro lab. Results are reported on every Monday and Thursday of the week.After careful consideration of the local infrastructure, robustness and cost of nuclear and non-nuclear assays, it is likely that RIA methodology will be the main workhorse of routine laboratory diagnostic services of NINMAS.Bangladesh J. Nuclear Med. 18(1): 64-68, January 2015